2018
DOI: 10.1126/science.aat3581
|View full text |Cite
|
Sign up to set email alerts
|

A single-photon switch and transistor enabled by a solid-state quantum memory

Abstract: Single-photon switches and transistors generate strong photon-photon interactions that are essential for quantum circuits and networks. However, the deterministic control of an optical signal with a single photon requires strong interactions with a quantum memory, which has been challenging to achieve in a solid-state platform. We demonstrate a single-photon switch and transistor enabled by a solid-state quantum memory. Our device consists of a semiconductor spin qubit strongly coupled to a nanophotonic cavity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
125
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 50 publications
1
125
0
1
Order By: Relevance
“…Furthermore, room temperature strong coupling could enable the development of chip‐based and broadly distributable platforms for technologies based on quantum transduction and quantum‐state control . Extension of nano‐cQED to the single photon limit would further enable quantum elements such as single‐photon switching, control of single photons by emitter states and single emitters by photons, and single‐photon optical transistors . Additionally, coherent control of the quantum state of an emitter through time domain Rabi flopping is required for preparation and read‐out of quantum states but has not yet been achieved using plasmonic nano‐cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, room temperature strong coupling could enable the development of chip‐based and broadly distributable platforms for technologies based on quantum transduction and quantum‐state control . Extension of nano‐cQED to the single photon limit would further enable quantum elements such as single‐photon switching, control of single photons by emitter states and single emitters by photons, and single‐photon optical transistors . Additionally, coherent control of the quantum state of an emitter through time domain Rabi flopping is required for preparation and read‐out of quantum states but has not yet been achieved using plasmonic nano‐cavities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the context of quantum memory applications, long‐lifetime emitters could serve as a way to preserve the polarization state of a photonic qubit for later use. More recently, the usefulness of long‐lifetime single emitters has been demonstrated in the form of single‐photon switching of a transistor enabled by a solid‐state quantum memory …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] These applications require the spin-state of the quantum dot to modulate the cavity reflectivity, allowing the spin to control the state of the reflected photons (e.g., polarization and frequency).Several studies have demonstrated such strong spin-photon interfaces between the electron spin of a charged quantum dot and cavity, 14-17 enabling optical nonlinearities such as Kerr rotations 16,17 and single-photon transistors. 15 These studies have relied on probabilistically charged quantum…”
mentioning
confidence: 99%